Ethylene oxide review: characterization of total exposure via endogenous and exogenous pathways and their implications to risk assessment and risk management. (2nd January 2021) - Kirman, CR; Li, AA; Sheehan, PJ; Bus, JS; Lewis, RC; Hays, SM
ABSTRACT: This review is intended to provide risk assessors and risk managers with a better understanding of issues associated with total exposures of human populations to ethylene oxide from endogenous and exogenous pathways. Biomonitoring of human populations and lab animals exposed to ethylene oxide has relied upon the detection of hemoglobin adducts such as 2-hydroxyethylvaline (HEV), which provides a useful measure of total exposure to ethylene oxide from all pathways. Recent biomonitoring data from CDC provide an excellent characterization of total exposure to ethylene oxide to the general U.S. population by demographic factors such as age, gender, and race as well as smoking habit, which might be comparable to previous measurements reported for humans and lab animals. The biochemical pathways including gastrointestinal (production by bacteria) and systemic (enzymatic production) pathways by which endogenous ethylene is generated and converted to ethylene oxide are described. The relative importance of endogenous pathways and exogenous pathways via ambient air or tobacco smoke was quantified based upon available data to characterize their relative importance to total exposure. Considerable variation was noted for HEV measurements in human populations, and important sources of variation for all pathways are discussed. Issues related to risk assessment and risk management of human populations exposed to ethylene oxide are provided within the context of characterizing total exposure, and data needs for supporting future risk assessment identified.